Characterization of Bottom Ash from the Combustion of Palm Oil Empty Fruit Bunches (EFB) - Amru Hamdi Fu’ad,; Amirnordin, Shahrin Hisham; Ahmad Jais Alimin,; Shahrul Azmir Osman,; Azian Hariri,; Norasikin Mat Isa,; Amir Khalid,; Mohd Faizal Tukimon,; Zulkifli Mohd Rosli,; Mohammad Faizal Jabbar, (International Journal of Integrated Engineering, 2025)
The palm oil industry generates large volumes of biomass waste, particularly Empty Fruit Bunches (EFB), which pose environmental disposal challenges but offer potential as a renewable energy source. This study focuses on the characterization and combustion analysis of bottom ash derived from pelletized EFB, with special attention to how combustion temperature affects ash quality at a fixed time duration. Pelletized EFB offers improved energy density and uniform combustion behavior compared to loose EFB. Combustion was conducted for 30 minutes at three different temperatures: 400°C, 600°C, and 800°C. The results showed that combustion temperature significantly influences ash yield and composition. Lower temperatures produced darker ash with higher residual carbon, while higher temperatures generated lighter ash with more fused and mineral-rich phases containing silicon, potassium, and calcium. XRD analysis confirmed a transition from simple crystalline phases at low temperatures to more complex silicate and glassy phases at higher temperatures, suggesting potential for construction-related applications. TGA revealed that major mass loss occurred between 200-375 °C due to decomposition of hemicellulose and cellulose, leaving about 33% inorganic residue forming the ash. Overall, this study highlights the critical role of combustion temperature in determining the physicochemical and mineralogical characteristics of EFB bottom ash and supports its potential for sustainable utilization within the palm oil industry.